Effects of packing shape and density on magnetic behavior of MnBi powder - Juntree, Puttamawan; Eknapakul, Tanachat; Pinitsoontorn, Supree; Songsiriritthigul, Prayoon (RMUTSB ACADEMIC JOURNAL, 2022)
In this work, the M-H hysteresis curves of manganese bismuth (MnBi) were studied as a function of packing shape and density measured by Vibrating Sample Magnetometer (VSM). MnBi powders were successfully prepared by sintering under vacuum at sintering temperature of 325 oC for 120 hrs at base pressure of 4×10-8 mbar. The MnBi phase identification and concentration were characterized by X-ray diffraction. The MnBi powder particles with size of less than 20 mm, which used in this work, were obtained by ball milling and followed by grid sieving. MnBi samples with different packing shapes were prepared by varying sample lengths with a fixed packing density of 6.366 g/cm3. In order to obtain the credible magnetic properties, the demagnetizing factor (N) was used to correct the hysteresis curves. The N value was estimated to be 0.416, 0.390, and 0.340 with corresponding energy product ((BH)max) of 1.04, 1.10 and 0.92 MGOe at sample heights of 0.35, 0.25 and 0.15 cm, respectively. Samples with different packing densities were determined by filling the equivalent mass in different volumes. The corrected (BH)max values of 1.29, 1.54 and 1.12 MGOe were obtained in the samples with packing densities of 7.427, 5.305 and 3.183 g/cm3, respectively. The M-H curves of MnBi with varied packing shapes were slightly different, while variations of MnBi with varied packing densities were obvious. The changes in hysteresis loop upon varying packing density could be explained by the bistable behavior. Their coercivity enhancements was ascribed by degree of particle rotation. Interestingly and unexpectedly, the maximum (BH)max was obtained at the measured length of 0.25 cm which may suggest the measurement optimization.